Ion-Induced Reactivity in Pyrene Clusters. (29th January 2015) - Gatchell, M; Delaunay, R; Maclot, S; Chen, T; Stockett, M H; Domaracka, A; Méry, A; Adoui, L; Zettergren, H; Rousseau, P; Cederquist, H; Huber, B A
Abstract: We report experimental indications of chemical reactions inside clusters of pyrene (C16 H10 ) molecules following collisions with 11.25 keV He+ - and 12.0 keV Ar 2+ ions. It appears that bond-forming reactions are more likely with the heavier projectile. We have also performed classical molecular dynamics simulations of these processes where we treat the interaction between the projectiles and all atoms in the cluster as well as non-dispersive and dispersive forces between all atoms in the cluster before, during and after the collision. The time step is typically 10 −17 s and the total simulation time 1 picosecond. The simulations were performed for a fixed cluster size with 36 pyrene molecules, although there is a broad range of cluster sizes in the experiment. Still, there is good qualitative agreement between the experimental and the simulated mass spectra exhibiting reaction products with masses between those of the C16 H10 - monomer and dimer in both cases. Additional studies of the influence of the projectile charge and mass is planned as well as simulations on longer time scales and as functions of cluster size.